PROSPEK PENGEMBANGAN PROGRAM KEMITRAAN DAN FAKTORFAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI BENIH BUNCIS PADA PROGAM KEMITRAAN (CONTRACTFARMING) PT. BENIH CITRA ASIA - Aji, Joni Murti Mulyo; Hariyati, Yuli; Agustina, Imaniar (9-772301-994005, 2013)
Beans (PhaseolusÂ  vulgaris .L.) have been known as an important vegetable for a long time. Although the use of green beans as daily consumption tends to decline, the demand as raw material in agribusiness industry and others tends to increase. This situation open the opportunity for PT. Benih Citra Asia (BCA), a horticulture breeding company, to collaborate with farmers producingÂ  seeds including green beans seedÂ  through contract farming arrangement. This research aims to identify opportunities and benefits of involving in a contract farming arrangement for farmers, factors affecting income, incomeâs value and farm management cost efficiency. This research was conducted in Wuluhan Sub District, Jember Regency. The data was analyzed by using SWOT analysis, the multiplier linear regression model, income analysis and R/C ratio. Results showed that: (1) contract-farming arrangement located in SWOT white area (ideal). It also indicated that there was strong opportunity and benefit for both parties involved. (2) Seed cost (X2), fertilizer costs (X3), labor costs (X5) and total production (X6) were found as factors influencing farmersâ income with significant level of 95%. (3) The average income per hectare of beans farming in Wuluhan Sub District Jember Regency was Rp. 5.248.213,10. (4) R/C ratio of this farm management was more than one (1,43), Â it indicated that the using of cost in green beans farm management was efficient.